Lifestyle and geographic insights into the distinct gut microbiota in elderly women from two different geographic locations. Issue 1 (December 2016) - Shin, Ji-Hee; Sim, Minju; Lee, Joo-Young; Shin, Dong-Mi
Abstract Background A large number of microorganisms reside within the gastrointestinal tract, especially in the colon, and play important roles in human health and disease. The composition of the human gut microbiota is determined by intrinsic host factors and environmental factors. While investigating environmental factors to promote human health is of great interest, few studies have focused on their effect on the gut microbiota. This study aimed to investigate differences in gut microbiota composition according to lifestyle and geographical area, even in people with similar genetic background. Methods We enrolled ten and nine elderly women in their seventies from island and inland areas, respectively. Fecal samples were obtained from individuals, and bacterial 16S ribosomal RNA genes were analyzed by next-generation sequencing to define the gut microbiota composition. We assessed their diet, which can influence the gut microbial community. We also conducted physical examination and determined the physical activity levels of the subjects. Results The inland subjects had a significantly higher rectal temperature, systolic blood pressure, and heart rate and a significantly lower physical activity score than the island subjects. Fecal samples from the island group showed a tendency to have greater microbial diversity than those from the inland group. Interestingly, the microbial community composition differed significantly between the two groups.Catenibacterium was enriched in subjects from the island area.Catenibacterium showed a negative correlation with rectal temperature and a positive correlation with the dietary level of animal fat. In contrast, Butyricimonas was enriched in the inland subjects. A positive correlation was found betweenButyricimonas and mean arterial pressure. Conclusions This study identified differences in the gut microbiota composition between elderly women from different parts of South Korea, and our findings suggest that further studies of the human gut microbiota should evaluate aspects of the living environment.